Revealing the thermodynamic driving force for ligand-based reductions in quinoids; conceptual rules for designing redox active and non-innocent ligands1. Issue 7 (15th July 2015) - Skara, G.; Pinter, B.; Geerlings, P.; De Proft, F.
<x xml:space="preserve">Abstract</x> The easy reduction of quinoid ligands is driven thermodynamically by superior M–L electrostatics and σ-bonding in the reduced form.